(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
An inorganic-organic hybrid material composed of tetrachlorocadmate as inorganic component and acetanilide as an organic moiety has been prepared by using solution growth through slow cooling process. The prepared material has been characterized by powder XRD peak profile pattern which results the existence of the material in monoclinic space group P2\(_1\)/c with cell dimensions of \(a = 7.571(2)\) \(Å\), \(b = 24.959(5)\) \(Å\), \(c = 19.666(4)\) \(Å\), \(α = γ = 90^°\), \(β = 90.017(2)^o\). The surface functionalities were analyzed by FESEM image analysis which depicts the average particle size of 6.731 \(μ\)m. The spatial agglomeration was observed through TEM image which predict that such materials has applications in energy storage devices.